The Relationship Between Total Quality Management and Patient Satisfaction in Healthcare Sector at Saudi Arabia - Alshareef, Huda Mosleh; Maajeeny, Rahaf; Judah, Maram Shaker; Alzaagi, Esraa Ahmed; Alkhuzaie, Khulood Hasan; Alsolami, Mastour Ateeq; Khogir, Suha Abdulraof; Almaki, Abdalhadi Omar; Baazeem, Mazen; Munshi, Wadie Kamel; Alwagdani, Ahmed Safar; Alsulami, Abdul Hamid Sweher (Journal of Ecohumanism, 2024)
Hospitals today are very different from those of the past, where attempts to guarantee the security and comfort of Hospitalized patients are governed by rules and laws. Advanced technology-using hospitals have been widespread around the world, including in Saudia Arabia, and have been serving a large patient population for many years. Saudia Arabia’s health sector is expanding quickly, resulting in significant Competition. For healthcare organizations to thrive, they must draw in and keep Clients. Consumers are essential to an organization’s existence and prosperity. Aim: to investigate the effects of total quality management (TQM) on patient satisfaction (PSAT). Methodology: a quantitative cross-sectional correlational study, a convenience sample of 380 in-patients receiving treatment at a governmental hospital, King Faisal Hospital in Saudi Arabia. Data was collected by using two questionnaires: total quality management (TQM) and patient satisfaction (PSAT) with data analysis conducted using Amoss26 and SPSS26. Conclusion: The findings revealed that total quality management positively influenced patient satisfaction. Limitation: Since there are fewer studies on total quality management in the healthcare sector than in manufacturing industries, this research makes a substantial contribution to the body of literature already in existence and merits additional study. Furthermore, this research offers significant perspectives for managers in the healthcare industry about strategic planning and decision-making procedures.